PENGARUH LATIHAN SQUAT JUMP TERHADAP POWER OTOT TUNGKAI PADA KENSHI RANDORI PUTRA SHORINJI KEMPO DOJO FMIPA UNIVERSITAS RIAU - Riadi, Bagus; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to knowthe effect of squat jump exercise toward the power of leg muscles inkenshirandori the men of shorinjikempo the dojo FMIPA the university of riau.Forms of this research is the experimental treatment (Experimental), withsampel of 5 people.Were obtained and collected through the pree test and post test before and after Squat Jump exercise using instrument Vertical Power Jump test, which aims to measure the power leg muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect of exercise Squat Jump to the power of leg muscle. Based on t test analysis produces TtabelThitung of 2,459 and 2,132, meaning Thitung>Ttabel. Based on the analysis of statistical data, there are an average Pree-test of 111,87and an average post-test 115,27, then the data is norma because Lhitung< Ltabel. Thus, there Effect of Squat Jump exercisetoward the power of leg muscle in kenshirandori the men of shorinjikempo the dojo FMIPA the university of riau.Keywords : Squat Jump, The Power Leg Muscle